Central Java Regional Police Cyber Public Relations Strategy in Improving the Institution's Image - Azzahra, Davina Widya; Wisudawaty, Hanna (Jurnal Ilmiah Komunikasi Makna, 2025)
Public Relations (PR) plays an important role in building an institution's image through strategic communication. In the Central Java Regional Police, Cyber Public Relations (CPR) is the main strategy in conveying information effectively to the public. CPR is used to educate the public about various police operations, such as traffic security during big days, to ensure transparency and openness of information. This study aims to analyze the Central Java Regional Police's CPR strategy in building a positive police image, improving communication with the public, and ensuring transparency of information in the digital era. CPR utilizes various digital platforms, such as Instagram, Facebook, Twitter, and the official Polda website, to establish more interactive and open communication. With a descriptive qualitative approach, this study found that CPR plays an important role in improving the police's image, strengthening relations with the public, and maintaining the institution's positive identity. This strategy allows the police to be more responsive to public aspirations and changes in digital trends. In the ever-evolving digital era, CPR is a strategic tool for the police to stay relevant, build public trust, and ensure more effective openness of information.